Impact of agri-horti landuse system on farm profitability and sustainability under rainfed conditions - GUPTA, MEENAKSHI; KOUR, SARABDEEP; BHARAT, RAJEEV; SHARMA, B.C.; KACHROO, D. (Journal of Soil and Water Conservation, 2022)
To assess the field applicability of agri-horti landuse system on farmer’s field under rainfed conditions of Jammu region, on-farm trial was established from kharif2015 to rabi 2017-18 in citrus orchard. At the citrus orchard, a rain water harvesting structure was prepared. By utilizing rainwater harvesting (RWH) technology as a supplementary source of water for crop production, various agricultural enterprises were integrated so that farmer gets higher yield and regular income. The results showed increase in yield of citrus fruit trees along with intercrops wheat (Triticum aestivum L.) and mustard (Brassica juncea L.) taken in rabi season and maize (Zea mays L.) and bajra (Pennisetum glaucum L.) taken in kharif season. The mean increase in fruit yield due to interventions, after three years of study was to the tune of 22.0 percent. Benefit cost ratio of fruit trees after three years of study, increased to 6.2 as compared to 4.68 without interventions. Mean yield of inter row crops due to various interventions increased by 34.0, 33.0, 50.0 and 48.0 percent for wheat, mustard, maize and bajra, respectively, than the yield obtained without interventions. The study showed that intercrops did not exert adverse effect on the growth and productivity of citrus fruits. The field crops intercropped in the orchard provided seasonal revenue to the farm family. Intercropping in citrus was effective in bringing improvement in the soil fertility, leading to a sustainable production system.